IL-1β and compressive forces lead to a significant induction of RANKL-expression in primary human cementoblasts = IL-1β und Kompression führen zu einer signifikanten Induktion der RANKL-Expression in primären humanen Zementoblasten - Diercke, Katja; Kohl, Annette; Lux, Christopher J.; Erber, Ralf (Journal of orofacial orthopedics, 2012)
The aim of this study was to investigate the response of primary human cementoblasts to conditions as they occur on the pressure side during orthodontic tooth movement.
Gesehen am 12.02.2019
Text in englischer und deutscher Sprache